Study status of care adherence and its related factors in patients undergoing - leila Rouhi Balasi; Ezat Paryad; Ehsan Kazemnezhad Leili; Shahnaz Booraki; Alimohammad SadeghiMeibodi; Nasir Nassiri Sheikhani (Guilan University of Medical Sciences, 2015)
Abstract Introduction: Coronary artery disease is one of the most common forms of cardiovascular disease. In attention to high prevalence of cardiovascular disease, coronary artery bypass grafting is a common technique for its treatment. Contrary to belief of most patients, this method has the effect of relief and not treatment. Therefore adherence to care instructions after surgery is very important. Several factors can affect the adherence of care instructions. Objective: This study aims to determine the status of adherence and its related factors in patients undergoing coronary artery bypass surgery. Methods: In this cross-sectional study, 217 patients referring to Dr Heshmat educational therapeutic center undergoing coronary artery bypass surgery in more than 6 months ago were selected by systematic random sampling method and studied through telephone interviews using the adherence of care instructions and illness perception questionnaire. For data analysis Chi-square and Fisher's exact test were used and multiple logistic regressions were used to determine the factors associated with adherence. Results: Findings showed that majority of patients had appropriate adherence to smoke cessation (88%) and physical activity (60.8%), but most study cases had inappropriate adherence to diet (88.5%). Regression results showed that predictive factors for adherence to smoke cessation included sex (P=0.003) and illness perception (P=0.04), and in regard to adherence of physical activity also sex(P<0.0001) and illness perception(P=0.057), and adherence to diet only sex(P=0.048) were indicated as predictors. Conclusion: According to the study results, adherence to care instructions is not complete. In attention to study results, rehabilitation of these patients after CABG is important and health care systems can prevent additional costs for patients and community by creating rehabilitation system.